Evaluation of concurrent use of Vitamin C and Niclosamide against methotrexate-induced liver injury in mice - Zainab Zeki; Ali Ismail Abdulla Al-Gareeb (Journal of the Pakistan Medical Association, 2024)
Objective: To examine the effect of using vitamin C and niclosamide together on liver damage caused by methotrexate. Method: The study was conducted at the Pharmacology Department and the Iraqi Center for Cancer and Medical Genetics Research, College of Medicine, Mustansiriya University, Baghdad, Iraq, from November 2020 to July 2021, and comprised albino mice who were randomly assigned to 5 groups. Group 1 comprised controls, groups 2 to 5 was received methotrexate, niclosamide 70mg/kg/day, vitamin C 100mg/kg/day, and a combination of niclosamide and vitamin C, respectively. Mice in groups 3, 4 and 5 also received an intraperitoneal injection of methotrexate 20mg/kg to induce hepatotoxicity. After 48 hours of the injection, the mice were sacrificed under chloroform anaesthesia. Cardiac blood samples were drawn for biochemical examination. The liver, after being washed, was divided into two parts; one part was taken for histological examination, and the other was preserved in formalin 10% for histopathological analyses. Data was analysed using SPSS 16. Results: Of the 35 mice, there were 7(20%) in each of the 5 groups. The overall age ranged between 9-12 weeks and weight between 18-38gm. The results show significant hepatoprotection ( p-value <0.05) produced by both niclosamide and Vitamin C separately, reflected by a decrease in ALP, ALT, and LDH, while the combination of (niclosamide and Vitamin C) showed no additive effect (p>0.05) on enhancement of liver function. Conclusion: Niclosamide alone was found to be superior than in combination with vitamin C for treating methotrexate-induced liver damage. Key Words: Methotrexate, Chloroform, Niclosamide, Intraperitoneal, Liver, Formaldehyde